Design, Synthesis, and Evaluation of Chalcone Derivatives as Multifunctional Agents against Alzheimer's Disease. Issue 11 (13th October 2021) - Wang, Xiao‐Qin; Zhou, Lu‐Yi; Tan, Ren‐Xian; Liang, Guo‐Peng; Fang, Si‐Xian; Li, Wei; Xie, Mei; Wen, Yu‐Hao; Wu, Jia‐Qiang; Chen, Yi‐Ping
Abstract: Fifteen chalcone derivatives 3a –3o were synthesized, and evaluated as multifunctional agents against Alzheimer's disease. In vitro studies revealed that these compounds inhibited self‐induced Aβ1‐42 aggregation effectively ranged from 45.9–94.5 % at 20 μM, and acted as potential antioxidants. Their structure‐activity relationships were summarized. In particular, (2 E )‐3‐[4‐(dimethylamino)phenyl]‐1‐(pyridin‐2‐yl)prop‐2‐en‐1‐one (3g ) exhibited an excellent inhibitory activity of 94.5 % at 20 μM, and it could disassemble the self‐induced Aβ1‐42 aggregation fibrils with ratio of 57.1 % at 20 μM concentration. In addition, compound 3g displayed good chelating ability for Cu 2+, and could effectively inhibit and disaggregate Cu 2+ ‐induced Aβ aggregation. Moreover, compound 3g exerted low cytotoxicity, significantly reversed Aβ1‐42 ‐induced SH‐SY5Y cell damage. More importantly, compound 3g remarkably ameliorated scopolamine‐induced memory impairment in mice. In summary, all the results revealed compound 3g was a potential multifunctional agent for AD therapy. Abstract :